Isolation of Indole Alkaloids from the roots of Kopsia Singapurensis Ridl. (Apocynaceae) and its Cytotoxic activity - Halimatussakdiah (Tanjong Malim, 2015)
Isolation of Indole Alkaloids from the roots of Kopsia Singapurensis Ridl. (Apocynaceae) and its Cytotoxic activity by Halimatussakdiah